Optimisation of microwave-assisted extraction of artocarpus integer peel pectin with choline chloride based deep eutectic solvent / Mohammad Amin Wan Chik ... [et al.] - Wan Chik, Mohammad Amin; Yusof, Rizana; Shafie, Muhammad Hakimin; Mohamed Hanaphi, Roziana; Nagoor Gunny, Ahmad Anas (Research Management Institute (RMI), 2023)
Extraction of pectin from natural resources using a biodegradable solvent is an alternative to wasteful and corrosive acidic extraction. Traditionally, attempts to extract pectin from biomass have resulted in low yields and a large consumption of corrosive solvents. Therefore, microwave-assisted extraction (MAE) with deep eutectic solvents (DES) of choline chloride and malonic acid (ChCl:MA) at a mole ratio of 1:2 was used in this study. The objective of this study was to extract pectin from Artocarpus integer peels (AIP) and to optimise the extraction conditions in terms of the percentage of DES, solid-to-liquid ratio of AIP to DES, microwave power, and extraction time. The results showed that the pectin yield increased as the percentage of DES, solid-to-liquid ratio, power, and time increased. The extraction of pectin up to 30.17 % with MAE was optimised at a 1:50 ratio, 50 W, 4 min, and 5 % DES. These results indicate that the proposed MAE-DES technique is excellent for extracting pectin with high yield from AIP.